Efektivitas Penerapan Pembelajaran Tematik Pada Siswa Slow Learners Mis Hi Achmad Syukur Daruba Kecamatan Morotai Selatan - Julia Ismail; Dewi Mulyanti Manompo (Peneliti.net, 2022)
This type of research is a qualitative research which aims to determine the use of thematic learning methods for slow learners at MIS HI Achmad Syukur Daruba, South Morotai District. The research was conducted from February 2022 to March 2022. The data in this study consisted of primary data and secondary data. Primary data was obtained through interviews with MIS Hi teachers. Achmad Syukur Daruba, South Morotai District, while secondary data was obtained through data that had been processed from other parties, namely with documents from the evaluation of students who experienced sloe learners. Data collection techniques in this study were carried out through observation, interviews, and documentation. Data analysis in this study used data presentation in the form of brief descriptions found during the research, drawing conclusions, and checking the validity of the data. The results showed that the number of students at MIS Hi Achmad Gratitude Daruba, South Morotai District, totaled 214 students, while overall students for Slow Learners MIS Hi Achmad Syukur Daruba, Morotai Selatan District, totaled 52 people where the most students were in class IV with a total of 12 students, while for the total Slow Learners students are at least in class V with a total of 4 students. While in total the Slow Learners were dominated by male students with a total of 29 students, while there were 23 female students. The highest percentage of slow leraners is in class IV with a total of 12 students, followed by class II and class III with a total of 10 students each, in class VI there are 9 students, class I with a total of 7 students and for the percentage the lowest number of slow learners is in class V, which is 4 students. Based on the explanations from the respondents, the researcher can draw the conclusion that Slow Learners students have retarded understanding of each subject given by the teacher, causing the grades obtained by students to be unsatisfactory.